Algorithm of Actions of the Prosecution After Detecting Undeclared Assets in the Course of Investigating the Receipt of Undue Advantage - Hudz, Vasyl (Problems of legality, 2026)
The detection of undeclared assets in the course of investigating the receipt of an unlawful benefit by public official poses challenges for pre-trial investigation authorities, and requires them to make certain procedural decisions. In order to outline this algorithm of appropriate actions, the article examines the legal mechanisms available to Ukrainian law enforcement agencies in such cases. It is important to stress that when investigating the receipt of unlawful benefits, it may be necessary to apply legal instruments that have been introduced into Ukrainian legislation only recently, and that might require substantial changes in the near future. The aim of this study is to examine the algorithm of actions that are applied when Ukrainian law enforcement agencies detect undeclared assets during the investigation of the receipt of unlawful benefits by an official. To achieve this objective, the study employed formal-legal, logical-legal, dialectical, descriptive, systematic and logical methods The results of the study show that in certain situations, pre-trial investigation authorities have different tactics at their disposal. These include providing evidence that an official has declared inaccurate information, gathering evidence for a lawsuit that aims at shoving that assets have not been acquired lawfully and that is geared at recovering them as state revenue, or proving illegal enrichment. It is the author’s conviction that the study also proves that current Ukrainian legislation contains provisions that allow for effectively countering violations of the law and responding appropriately to the ownership or use of undeclared property by public officials. The author is also of the opinion that further research should focus on finding ways to improve legislation through the prism of judicial and law enforcement practice that will be developed in the future. This will help to improve the legal instruments described, adapt Ukrainian legislation to the legislation of advanced democracies, and contribute to the establishment of legality and the rule of law.